1998
DOI: 10.1007/s002800050787
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism, excretion and pharmacokinetics of a single dose of [ 14 C]-raltitrexed in cancer patients

Abstract: Raltitrexed (Tomudex) is a specific inhibitor of thymidylate synthase and has recently been licensed in Europe for use in the treatment of advanced colorectal carcinoma. This study evaluated the metabolism, excretion and pharmacokinetics after a single dose of 3.0 mg/m2 [14C]-raltitrexed in patients with advanced solid malignancies not amenable to curative therapy. From April 1994 to July 1995, nine patients (six men and three women) were recruited into the study. Pharmacokinetics analysis was performed during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…Raltitrexed is commonly administered as a 15 min i.v. infusion and the β-and γ-half-lives are 2 and >10 h. 4,5) Clinical studies have shown that the dose-limiting toxicities of raltitrexed involve myelosuppression, malaise and gastrointestinal toxicity. 4,6) Raltitrexed has promising therapeutic activity against colon cancer and other solid tumors.…”
mentioning
confidence: 99%
“…Raltitrexed is commonly administered as a 15 min i.v. infusion and the β-and γ-half-lives are 2 and >10 h. 4,5) Clinical studies have shown that the dose-limiting toxicities of raltitrexed involve myelosuppression, malaise and gastrointestinal toxicity. 4,6) Raltitrexed has promising therapeutic activity against colon cancer and other solid tumors.…”
mentioning
confidence: 99%
“…Recent pharmacokinetic studies suggest that up to 60% of raltitrexed clearance is accounted for by renal excretion (Clarke et al, 1996;Beale et al, 1998). It is therefore of interest that renal toxicity with the combination of raltitrexed and cisplatin was minimal.…”
Section: Discussionmentioning
confidence: 99%
“…The antifolates, like natural folates, are eliminated via the kidney (Azarnoff et al, 1974;Sessa et al, 1988;Beale et al, 1998;Rinaldi et al, 1999). Despite the dominant role of FRs in renal elimination of natural folates, their involvement in the renal elimination of antifolates has not been studied.…”
Section: Discussionmentioning
confidence: 99%